What has been studied on cryptocurrencies in Brazil: A systematic literature review (Research, Society and Development, 2024)
The objective of this study was to identify the researchers and institutions that study cryptocurrencies in Brazil, as well as what is being studied about cryptocurrencies in Brazil. The InOrdinatio Method was used, aiming to equate impact factor, number of citations, and year of publication of each article, allowing studies to be ordered according to these scientific parameters. Results: The first article meeting the research criteria was published in 2015, with half of the papers concentrated in 2017, and one edition dedicated to law and the digital world. No author or institution published more than one paper in the period analyzed, highlighting private institutions in the southern and southeastern regions. With regard to the topics covered, although it focused on bitcoin, it analyzed concepts, legal aspects, regulation, tax aspects, and the use of blockchain. The proposed criteria limited the number of studies analyzed, as many Brazilian journals are not indexed in international indexes such as Journal Citation Reports (JCR), Scientific Journal Rankings (SJR) (Scimago), CiteScore. Conclusion: The study contributes to the academic community through the application of a systematic literature review, presenting the main contributions on a topic that has been gaining the spotlight in the economic, tax, legal, and other areas.